The Gateway to Computer Science Excellence

0 votes

F(A,B,C)=AB+AC+BC

F(A',B',C')=A'B'+A'C'+B'C'

F(A',B,C')=A'B+A'C'+BC'

F(A,B',C')=AB'+AC'+B'C'

Now, F(A',B',C') . F(A',B,C') . F(A,B',C') = [A'B'+A'C'+B'C'] . [A'B+A'C'+BC'] . [AB'+AC'+B'C']

= [ A'B'C'+A'BC'+A'C' ] . [AB'+AC'+B'C'] (By Applying Distributive)

= [A'B'C'+A'C'] . [AB'+AC'+B'C'] (By Applying Absorption Law)

= A'B'C'

- All categories
- General Aptitude 1.9k
- Engineering Mathematics 7.5k
- Digital Logic 2.9k
- Programming and DS 4.9k
- Algorithms 4.3k
- Theory of Computation 6.2k
- Compiler Design 2.1k
- Databases 4.1k
- CO and Architecture 3.4k
- Computer Networks 4.1k
- Non GATE 1.5k
- Others 1.5k
- Admissions 595
- Exam Queries 576
- Tier 1 Placement Questions 23
- Job Queries 72
- Projects 17

50,650 questions

56,236 answers

194,255 comments

95,858 users